A New Model of Quantum Dot Light Emitting-Absorbing Devices - Neidhardt, H.; Wilhelm, L.; Zagrebnov, V.A. (Журнал математической физики, анализа, геометрии, 2014)
Motivated by the Jaynes–Cummings (JC) model, we consider here a quantum dot coupled simultaneously to a reservoir of photons and two electric leads (free-fermion reservoirs). This new Jaynes–Cummings-leads (JCL)-type model makes it possible that the fermion current through the dot creates a photon flux, which describes a light-emitting device. The same model also describes a transformation of the photon flux into the current of fermions, i.e., a quantum dot light-absorbing device. The key tool to obtain these results is the abstract Landauer–Büttiker formula. Мотивируемые моделью Джейнса-Каммингса (ДК), рассматриваем квантовую точку, соединенную одновременно с резервуаром фотонов и двумя электродами (нефермионными резервуарами). Новая модель Джейнса-Каммингса для электродов (ДКЭ) позволяет фермионному току, проходящему через точку, создавать поток фотонов, что является характеристикой светоизлучающего устройства. Та же самая модель используется для описания трансформации потока фотонов в ток фермионов, т.е. квантово-точечного светопоглощающего устройства. Ключевым средством для получения результатов стала абстрактная формула Ландауэра-Буттикера.